2001
DOI: 10.1016/s0014-5793(01)03223-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of 2‐methyl‐6‐phytylbenzoquinone methyltransferase in determining tocopherol composition in Synechocystis sp. PCC6803

Abstract: A putative 2-methyl-6-phytylbenzoquinone (MPBQ) methyltransferase gene, SLL0418, was identified from the Synechocystis PCC6803 genome based on its homology to previously characterized Q Q-tocopherol methyltransferases. Genetic and biochemical evidence confirmed open reading frame (ORF) SLL0418 encodes a MPBQ methyltransferase. An SLL0418 partial knockout mutant accumulated L L-tocopherol with no effect in the overall tocopherol content of the cell. In vitro assays of the SLL0418 gene expressed in Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 14 publications
1
65
1
1
Order By: Relevance
“…Previous studies have demonstrated that tocopherol biosynthetic enzymes are remarkably conserved in both primary sequence and activity in cyanobacteria and plants (Norris et al, 1998;Shintani and DellaPenna, 1998;Collakova and DellaPenna, 2001;Porfirova et al, 2002;Shintani et al, 2002;Sattler et al, 2003). In this regard, the low sequence identity of MPBQ/ MSBQ MT in Arabidopsis and Synechocystis sp PCC6803 stands in stark contrast to other pathway enzymes and suggests that although similar, fundamental differences exist in tocopherol and PQ synthesis in cyanobacteria and plants.…”
Section: New Insights Into the Synthesis And Regulation Of Tocopherolmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that tocopherol biosynthetic enzymes are remarkably conserved in both primary sequence and activity in cyanobacteria and plants (Norris et al, 1998;Shintani and DellaPenna, 1998;Collakova and DellaPenna, 2001;Porfirova et al, 2002;Shintani et al, 2002;Sattler et al, 2003). In this regard, the low sequence identity of MPBQ/ MSBQ MT in Arabidopsis and Synechocystis sp PCC6803 stands in stark contrast to other pathway enzymes and suggests that although similar, fundamental differences exist in tocopherol and PQ synthesis in cyanobacteria and plants.…”
Section: New Insights Into the Synthesis And Regulation Of Tocopherolmentioning
confidence: 99%
“…Growth, induction, cell harvesting, and extraction of engineered proteins in E. coli were performed as described by Shintani et al (2002). Cells carrying an empty pET30A vector also were induced as a negative control.…”
Section: Escherichia Colimentioning
confidence: 99%
See 1 more Smart Citation
“…Insertional inactivation of the genes encoding each enzyme of the pathway has resulted in a series of mutants in which the content and composition of tocopherol species vary. For example, the slr0089 mutant accumulates only g-tocopherol (Shintani and DellaPenna, 1998), the sll0418 mutant accumulates 30% of the wild-type level of a-tocopherol and a small amount of b-tocopherol (Shintani et al, 2002;Cheng et al, 2003), whereas the slr1736 mutant lacks all tocopherols (Collakova and DellaPenna, 2001). In light of the established antioxidant activity of a-tocopherol, one would expect that a loss or reduction of a-tocopherol would lead to an obvious phenotypic difference between the wild-type and mutant strains.…”
mentioning
confidence: 99%
“…As one of the critical enzymes involved in plant vitamin E biosynthesis, 2-methyl-6-phytyl-1,4-benzoquinol methyltransferase (MPBQ MT) can catalyze MPBQ to generate 2,3-dimethyl-6-phytyl-1,4-benzoquinone (DMPBQ). MPBQ and DMPBQ, however, are cyclized by tocopherol cyclase to yield δ-and γ-tocopherol, respectively, which are subsequently further converted to β-and α-tocopherol by γ-tocopherol methyltransferase (γ-TMT) (Shintani and DellaPenna, 1998;Porfirova et al, 2002;Shintani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%